International models of accreditation and certification for hospitals with a focus on nursing: a scoping review - Carolin Gurisch; Joan Kleine; Claudia Bettina Maier (BMC, 2024)
Abstract Background Quality assurance in hospitals is essential for ensuring patient safety, quality of care and efficiency. The nursing profession is a key contributor to healthcare quality, yet, a comprehensive overview and comparison of the role and scope of nursing as part of accreditation and certification schemes has been lacking. The aim was to identify if and to what extent international accreditation or certification schemes focus on nursing, and to compare their conceptual models and outcome indicators. Methods A scoping review was conducted. A search strategy was developed together with a librarian and carried out in January 2024 in Medline, CINAHL, Web of Science Core Collection, Cochrane Reviews and Google Scholar. Additionally, authoritative websites of accreditation/certification holders were searched. Inclusion criteria were studies on international accreditation or certification schemes for hospital settings with relevance to nursing published in English or German. Screening and data analysis adhered to the Joanna Briggs Institute's methodology, with reporting following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guideline (PRISMA-ScR). Results The search identified 17.315 records. After removing duplicates and screening of titles/abstracts, 336 full-texts remained. A total of 124 studies were included, identifying seven international accreditation/certification schemes: European Foundation for Quality Management, Evaluation and Quality Improvement Program, International Organization for Standardization 9001, Joint Commission International®, Magnet Recognition Program®, Pathway to Excellence® Program, Qmentum®. The different schemes ranged from nursing-specific to having no specific focus on, but relevance for, nursing and varied in their topics, focus on structure, process and outcome quality and structure and content of requirements. Additionally, outcome indicators varied, with differences in the extent to which indicators were nurse-sensitive, compulsoriness of data collection, and use of external benchmarking. Conclusions The seven international schemes show large conceptual variations as to their focus on nursing and differences in the degree of nurse-specific outcome indicators. Hospital and nursing managers, policymakers, patients and the public need to understand the content and outcome dimensions of the schemes when making decisions or assessing hospital quality data.